Roles of Aquaporins in Setaria viridis Stem Development and Sugar Storage - McGaughey, Samantha A.; Osborn, Hannah L.; Chen, Lily; Pegler, Joseph L.; Tyerman, Stephen D.; Furbank, Robert T.; Byrt, Caitlin S.; Grof, Christopher P. L. (Frontiers in Plant Science, 2016)
Setaria viridis is a C4 grass used as a model for bioenergy feedstocks. The elongating internodes in developing S. viridis stems grow from an intercalary meristem at the base, and progress acropetally towards fully expanded cells that store sugar. During stem development and maturation, water flow is a driver of cell expansion and sugar delivery. As aquaporin proteins are implicated in regulating water flow we analysed elongating and mature internode transcriptomes to identify putative aquaporin encoding genes that had particularly high transcript levels during the distinct stages of internode cell expansion and maturation. We observed that SvPIP2;1 was highly expressed in internode regions undergoing cell expansion, and SvNIP2;2 was highly expressed in mature sugar accumulating regions. Gene co-expression analysis revealed SvNIP2;2 expression was highly correlated with the expression of five putative sugar transporters expressed in the S. viridis internode. To explore the function of the proteins encoded by SvPIP2;1 and SvNIP2;2 we expressed them in Xenopus laevis oocytes and tested their permeability to water. SvPIP2;1 and SvNIP2;2 functioned as water channels in X. laevis oocytes and their permeability was gated by pH. Our results indicate that SvPIP2;1 may function as a water channel in developing stems undergoing cell expansion and SvNIP2;2 is a candidate for retrieving water and possibly a yet to be determined solute from mature internodes. Future research will investigate whether changing the function of these proteins influences stem growth and sugar yield in S. viridis.